Pathogenesis and characterization of hyperglucagonemia in the uremic rat. - Emmanouel, D S (1976)
The pathogenesis of hyperglucagonemia and of the alterations in the pattern of circulating immunoreactive glucagon (IRG) associated with renal insufficiency was studied in rats in which a comparable degree of uremia was induced by three different methods, i.e., bilateral nephrectomy, bilateral ureteral ligation, and urine autoinfusion. Nephrectomized and ureteral-ligated rats were markedly hyperglucagonemic (575 +/- 95 pg/ml and 492 +/- 54 pg/ml, respectively), while IRG levels of urine autoinfused animals (208 +/- 35 pg/ml) were similar to those of control rats (180 +/- 26 pg/ml), indicating that uremia per se does not account for the hyperglucagonemia observed in renal failure. Similarly, plasma IRG composition in this group of animals was indistinguishable from that of controls, in which 88.2 +/- 5.9% of total IRG consisted of the 3,500-mol wt fraction. The same component was almost entirely responsible (82.6 +/- 4.1%) for the hyperglucagonemia observed in ligated rats, while it accounted for only 57.6 +/- 5.0% of the circulating IRG in nephrectomized animals. In the latter group, 36.8 +/- 6.6% of total IRG had a mol wt of approximately 9,000, consistent with a glucagon precursor. This peak was present in samples obtained as early as 2 h after renal ablation and its concentration continued to increase with time reaching maximal levels at 24 h. These results confirm that the kidney is a major site of glucagon metabolism and provide evidence that the renal handling of the various circulating IRG components may involve different mechanisms. Thus, the metabolism of the 3,500-mol wt fraction is dependent upon glomerular filtration, while the uptake of the 9,000-mol wt material can proceed in its absence, as long as renal tissue remains adequately perfused. This finding suggests that the 9,000-mol wt component may be handled by peritubular uptake.